Digital Comic Based on PMRI on the Perimeter and Area of Plane Figures for Fourth Grade Elementary School Students (Jurnal Ilmiah Sekolah Dasar, 2025)
Mathematics learning often faces challenges in delivering abstract concepts, such as perimeter and area of plane figures, due to the lack of innovative learning media. This study aims to develop a learning medium and analyze its validity and effectiveness in improving students' learning outcomes. The study employs the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) with elementary school fourth-grade students as the research subjects. Data were collected through interviews, validation questionnaires, and multiple-choice tests. The data analysis method involves a quantitative descriptive approach to describe the data obtained from questionnaires and tests regarding the feasibility of the media from the perspective of experts and students. Additionally, a one-sample t- test was conducted to compare test results before and after the use of the media. The validation results indicate that the media has excellent quality, with average validation scores from subject matter experts, design experts, and media experts of 95.45%, 90%, and 93.75%, respectively. The effectiveness test results show a significant improvement in students' learning outcomes, with an average post-test score of 79, higher than the average pre-test score of 63. The t-test results indicate tcalculated = 2.10 > ttable = 1.70. This media is effective in enhancing students' understanding of perimeter and area concepts through an engaging contextual approach. The study concludes that the PMRI-based digital comic media is valid, feasible for use, and effective in mathematics learning. The implication is this media can be adapted for various other learning materials to support a more interactive, contextual, and engaging learning experience.